2007
DOI: 10.1007/978-3-540-74690-4_38
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Multi-objective Optimization of Spiking Neural Networks

Abstract: Abstract. Evolutionary multi-objective optimization of spiking neural networks for solving classification problems is studied in this paper. By means of a Paretobased multi-objective genetic algorithm, we are able to optimize both classification performance and connectivity of spiking neural networks with the latency coding. During optimization, the connectivity between two neurons, i.e., whether two neurons are connected, and if connected, both weight and delay between the two neurons, are evolved. We minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It has been shown that the multiobjective approach is more promising in alleviating forgetting than its single-objective counterpart. The idea of Pareto-optimality can also be extended to the study on connectivity and complexity [91], [92] of general networks, and to the research on structure and functionality of spiking neural networks [93], [94]. His current research interests include topics from systems biology and computational intelligence such as evolutionary system design and structure optimization of adaptive systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the multiobjective approach is more promising in alleviating forgetting than its single-objective counterpart. The idea of Pareto-optimality can also be extended to the study on connectivity and complexity [91], [92] of general networks, and to the research on structure and functionality of spiking neural networks [93], [94]. His current research interests include topics from systems biology and computational intelligence such as evolutionary system design and structure optimization of adaptive systems.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results have proved that the Memetic Harmony Search Multi-Objective Differential Evolution with Evolving Spiking Neural Network (MEHSMODE-ESNN) gives better results in terms of accuracy and network structure. Unlike previous study mentioned earlier in Jin [14] and other single objective studies [18,19], this paper deals with an improved multi objective method to obtain simple and accurate ESNN. The proposed method evolves toward optimal values defined by several objectives with model accuracy and ESNN's structure to improve performance for classification problems.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that one Multi-Objective Evolutionary Algorithms (MOEAs) was used and only for SpikeProp learning, most of the related work which use Multi-Objective Genetic Algorithms (MOGAs) is by Jin et al [14]. Both classification performance and connectivity of SNN with latency coding are optimized by MOGA.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown in [13] and in our previous work [14], [15] that the rate of convergence may be increased by using techniques such as “behavioral memory” developed by de Garis [16] and “staged evolution” developed by Lewis [17]. GAs have previously been used as learning rules for spiking neural networks acting as classifiers [18], [19]. The work presented in this paper differs in that GAs are used to configure the dynamics of pattern generator networks whose outputs are sustained rhythmic patterns.…”
Section: Introductionmentioning
confidence: 99%